Pengaruh Suhu, Kelembaban Dan Kecepatan Angin Air Conditioner (AC) Terhadap Jumlah Angka Kuman Udara Ruangan - Ginting, Daria BR; Santosa, Imam; Trigunarso, Sri Indra (Department of Health Analyst, Politeknik Kesehatan, Kementerian Kesehatan Tanjungkarang, 2022)
A room that uses an Air Conditioner (AC) is one of the breeding grounds for air microorganisms, therefore it is necessary to have a number of germs in the room so as not to cause airborne disease. The purpose of this study was to determine the effect of temperature, humidity, and wind speed on the number of germs in an air-conditioned room. This type of research is an experimental consisting of 3 dependent variables and 1 independent variable with a cross-sectional research design. Laboratory room air samples were taken by the BRAB method, 12 times in a row. Sampling of the air using an air sampling pump. The results of the study showed that there was a fairly close relationship and a significant effect on temperature with the number of germs (p value = 0.005), with a temperature effect of 20.9%. There is a relationship and influence between humidity and germ numbers (p value = 0.000), with a humidity effect value of 31.9%. There is a relationship and influence between wind speed and germ numbers (p value = 0.009), with a wind speed effect of 18.5%. There is a simultaneous effect of temperature, humidity, and wind speed on the germ number of 33.6%.